Noise, Water, Meat: A History of Sound in the Arts - Kahn, Douglas (Massachusetts MIT Press, 1999)
This interdisciplinary history and theory of sound in the arts reads the twentieth century by listening to it?to the emphatic and exceptional sounds of modernism and those on the cusp of postmodernism, recorded sound, noise, silence, the fluid sounds of immersion and dripping, and the meat voices of viruses, screams, and bestial cries. Focusing on Europe in the first half of the century and the United States in the postwar years, Douglas Kahn explores aural activities in literature, music, visual arts, theater, and film. Placing aurality at the center of the history of the arts, he revisits key artistic questions, listening to the sounds that drown out the politics and poetics that generated them. Artists discussed include Antonin Artaud, George Brecht, William Burroughs, John Cage, Sergei Eisenstein, Fluxus, Allan Kaprow, Michael McClure, Yoko Ono, Jackson Pollock, Luigi Russolo, and Dziga Vertov.